Education on Pandemic Condition: The Utilization of SPADA UNRAM and Natural Laboratory in Science Learning - Shazali, Muhammad; Ibrahim, Ibrahim; Wahdah, Nova Fitriani (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2023)
Education is one of the most affected areas by the Covid-19 pandemic, especially learning. This learning is new in the PGSD Study Program at FKIP Mataram University, so monitoring and evaluation are needed. This research aims to describe the process and students' learning outcomes through the implementation of SPADA Unram and the Natural Laboratory. The research sample comprised 63 students who took Basic Natural Sciences or Ilmu Alamiah Dasar (IAD) courses—data collected for eight weeks in October–December. Data about activity and student learning outcomes include (1) the activeness in discussion forums, (2) the discipline in collecting assignments, (3) the skills in completing assignments, and (4) the ability to complete quizzes. Descriptive statistics analyzed data to determine the mean and proportion. Only a tiny proportion (<50%) of students participated in discussion forums. From the disciplinary aspect, the balance of disciplined students is the largest, but many are still not disciplined in uploading assignments at SPADA Unram. Students' skills in completing tasks are excellent, but their ability to complete quizzes is in the fair category. Indicates that improvements are needed to maintain and improve the quality of science learning processes and outcomes during the pandemic.